(untitled) (Bioagro, 2025)
Common bean (Phaseolus vulgaris L.) is one of the most widely cultivated legumes worldwide due to its high nutritional value and role in food security. In Peru, its production in the Chincha Valley is vital for small and medium-scale farmers, serving as a key source of income. However, its productivity depends on agroclimatic and genetic factors. This study evaluated the performance of nine bean lines in the Chincha Valley to identify materials with greater productive potential. A Randomized Complete Block Design (RCBD) was used, assessing 14 traits through statistical analyses such as ANOVA, Pearson correlation coefficient, Principal Component Analysis (PCA), and hierarchical clustering. The PCA explained 40 % of the total variability in the first two dimensions. The first (23.3 %) was associated with yield components, while the second (16.7 %) was related to phenology, 100-seed weight, and pod length. The 100-seed weight showed a positive correlation with pod length (r=0.80) and a negative correlation with days to harvest maturity (r =-0.56). Can D8120 and Arbolito (cluster A) were the most productive lines (1402.75 and 1511.00 kg·ha⁻¹), with an intermediate 100-seed weight (49.30-51.70 g). Larán Mejorado (cluster B) stood out for its larger seed size and intermediate yield. These findings are keys for selecting high-yielding lines and incorporating them into breeding programs.